(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic kidney disease (CKD) is associated with immune dysfunction and chronic inflammation, leading to significant alterations in the oral mucosa. The accumulation of uremic toxins results in dysregulation of proinflammatory cytokines, oxidative stress, and impaired leukocyte function, contributing to an increased risk of periodontal disease, oral ulcers, and infections. This review examines the immunological and inflammatory pathways affected by uremic toxins and discusses potential clinical interventions aimed at improving oral health outcomes in CKD patients.